LEARNING METHODS OF MORALS AQEEDAH IN MAN KUTA BARO LAM ATEUK ACEH BESAR - Murni, Murni (STKIP An-Nur, 2019)
The background of the problem in this research is the method used in the learning process to date has not given maximum results.The purpose of this study was to determine the methods used in learning of morals aqeedah in MAN Kuta Baro Lam Ateuk Aceh Besar. The method used is a descriptive analysis method that is analyzing the collected data. Meanwhile, data collection techniques were carried out through library research and field research through observation, interviews and questionnaire distribution.Â Morals aqeedah material taught at Man Kuta Baro Lam Ateuk Aceh Besar is Islamic aqeedah including aqeedah (faith),sharia'at (worship), morals (Ihsan).The results of the study showed the method of teaching morals aqeedah by the teacher at MAN Kuta Baro using the lecture and question and answer method. The application of morals aqeedah learning to MAN Kuta Baro Lam Ateuk Aceh Besar through a good example from the teacher, and through creating a positive atmosphere for students.Â Keywords: Learning Methods; MoralsÂ Aqeedah